PSYCHOLOGICAL BENEFITS OF EXERCISE AND PHYSICAL ACTIVITY IN OLDER ADULTS - Petra Dolenc; Mojca Petrič (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2018)
While regular physical activity has been shown to positively impact health and physical functioning across all age groups an active lifestyle may in particular have beneficial effects in advanced age. The objective of this article is to provide a brief overview of a contemporary research on the benefits of physical activity for psychological health and quality of life in the elderly. Older adults are more vulnerable than other age groups regarding mental health problems, such as depression and anxiety. Many cross-sectional and experimental studies discussed in the article confirm the importance of a physically active lifestyle for preventing or reducing mental health problems and improving the quality of life among elderly people. Keywords: mental health, physical activity, quality of life, late adulthood